Intra-group conflict and teamwork quality: The moderating role of leadership styles - Petru L. Curşeu (Administrative Sciences, 2011)
The study examines the extent to which task and relations oriented leadership moderate the impact of task and relationship conflict on teamwork quality. In a sample of 37 teams, the study shows that relationship oriented leadership is beneficial for dealing with relationship conflict, but it does not have the expected positive interaction effect with task conflict. The main practical implication of the results is that in order to mitigate the negative effects of intra-group conflict on teamwork quality the leadership style should fit the type of disagreement (task versus relational) predominantly experienced by the teams.
Keywords: 350; intra-group conflict; relations and task oriented leadership; group processes